Mystic lands. Peru & Egypt [videorecording (DVD)]. - Olmos, Edward James; Duncan, Chip (Mystic lands (Television program), 2006)
Peru: Kingdom in the clouds: Considered to be the most significant archaeological site on the South American continent, Machu Picchu was built and then abandoned by the Inca after only 100 years. The influence of the Inca spiritual beliefs on their lifestyle, architecture and astronomical achievements will be explored in the ruins of Machu Picchu and the spiritual centers of Peru's Sacred Valley, including Ollantaytambo and Pisac.